Optimizing Wound Healing in Radial Forearm Donor Sites: A Comparative Study of Ulnar-Based Flap and Split-Thickness Skin Grafting - Adam Galazka; Katarzyna Stawarz; Karolina Bienkowska-Pluta; Monika Paszkowska; Magdalena Misiak-Galazka (Biomedicines)
Background: The radial forearm free flap (RFFF) is a common technique in head and neck reconstructive surgery. This study aimed to compare the clinical and biochemical outcomes of wound healing following ulnar-based transposition flap (UBTF) versus split-thickness skin grafting (STSG) for donor site closure, with a particular emphasis on tissue regeneration. Materials and Methods: A total of 24 patients (6 women, 18 men), underwent RFFF reconstruction. The donor site was closed using the UBTF technique in 10 cases, while STSG was performed in 14 cases. Postoperative complications—including necrosis, edema, hematoma, infection, and wound dehiscence—along with healing times were assessed daily during the first seven postoperative days and at monthly follow-ups over six months. Pre- and postoperative biochemical analyses included hemoglobin (HB), white blood cell count (WBC), platelets (PLT), albumin, and C-reactive protein (CRP) levels. An aesthetic evaluation of the flap was also performed. Results: The two groups were homogeneous. Postoperative complications occurred more frequently in the STSG group, which also demonstrated significantly longer healing times (p = 0.0004). In contrast, the UBTF group showed significantly better aesthetic outcomes in terms of skin color (p = 0.000021), skin texture (p = 0.000018), and flap stability (p = 0.0398). Additionally, pre- and postoperative PLT counts were significantly higher in the UBTF group (p = 0.001 and p = 0.043, respectively). Conclusions: While STSG remains a well-established method for forearm donor site closure following RFFF harvest, this study demonstrates that UBTF is a viable alternative associated with better clinical and aesthetic outcomes.